The seasonal evolution of shelf water masses around Bouvetøya, a sub-Antarctic island in the mid-Atlantic sector of the Southern Ocean, determined from an instrumented southern elephant seal - Lowther, Andrew D.; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
Our study makes use of a fortuitous oceanographic data set collected around the remote sub-Antarctic island of Bouvetøya by a conductivity–temperature–depth recorder (CTD) integrated with a satellite-relayed data logger deployed on an adult female southern elephant seal (Mirounga leonina) to describe the seasonal evolution of the western shelf waters. The instrumented seal remained in waters over the shelf for 259 days, collecting an average of 2.6 (±0.06) CTD profiles per day, providing hydrographic data encompassing the late austral summer and the entire winter. These data document the thermal stratification of the upper water layer due to summer surface heating of the previous year's Antarctic Surface Water, giving way to a cold subsurface layer at about 100 m as the austral winter progressed, with a concomitant increase in salinity of the upper layer. Upper Circumpolar Deep Water was detected at a depth of approximately 200 m along the western shelf of Bouvetøya throughout the year. These oceanographic data represent the only seasonal time series for this region and the second such animal–instrument oceanographic time series in the sub-Antarctic domain of the Southern Ocean.
Publisher: Routledge
Keywords: AABW; Bouvetøya; biotelemetri; hydrografi; marin biologi; oseanografi; seler

Temporal shift in the isotopic niche of female Antarctic fur seals from Bouvetøya - Tarroux, Arnaud; Lowther, Andrew D; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
The Antarctic fur seal (Arctocephalus gazella) is a key marine predator in the Southern Ocean, a region that has recently started to show changes as a result of global climate change. Here, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses on whole blood and plasma samples were used to examine the isotopic niche of lactating female Antarctic fur seals. Using recently developed Bayesian approaches to determine changes in isotopic niche, a significant increase in δ 13 C and δ 15 N was found between 1997 and 2015; this change occurred at an average rate of 0.067‰ (δ 13 C) and 0.072‰ (δ 15 N) per year over this period. This suggests that a marked isotopic niche shift has occurred over this period, which very likely corresponds to a shift in diet towards prey at a higher trophic level, such as fish (replacing krill). Although our sampling design prevented us from exploring a seasonal trend in a conclusive manner, our data suggest that concurrent increases in δ 13 C and δ 15 N might occur as the breeding season progresses. At a seasonal scale, an average decrease of −0.7‰ per month (95% confidence interval=[−0.9; −0.6]) in δ 13 C might have occurred, concurrently with an average increase of 1.1‰ per month in δ 15 N. The results of this study constitute the first isotopic assessment for female Antarctic fur seals from Bouvetøya and provide a baseline for the use of this predator species as a sentinel of the marine trophic system in one of the least studied areas within this species' distributional range.
Publisher: Routledge
Keywords: Bouvetøya; Sørishavet; klimaendringer; krill; marin biologi; pelsseler; plankton; stabile isotoper; zoologi

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Long-range migration of a chinstrap penguin from Bouvetøya to Montagu Island, South Sandwich Islands - Biuw, Martin; Lydersen, Christian; Nico de Bruyn, P. J.; Arriola, Aline; Hofmeyr, Greg G. J.; Kritzinger, Petrus; Kovacs, Kit M. (Antarctic Science, 2010)
We describe a long-range migration of a pre-moulting adult chinstrap penguin from Bouvetøya, a small relatively recently established colony, to the South Sandwich Islands, where large, established colonies of this species reside. The trip lasted around three weeks, covered ∼3600 km, and the time of arrival was consistent with the annual moult. The bird did not travel along the shortest path or along a constant bearing, but instead followed what appeared to be a series of two or three rhumb lines of constant bearing. Small southward and northward deviations from the general path were consistent with local water currents. Travel speeds were high during daylight but decreased at night, suggesting that resting or opportunistic feeding occurred preferentially at night. While long-range winter migrations of chinstraps to feeding areas in the vicinity of distant colonies have been previously described, this is the first observation of such a trip during the period between breeding and moulting, and the first record of an individual actually arriving at one of these distant colonies. This has implications for understanding population structure and management of this important Southern Ocean predator.
Publisher: Cambridge University Press
Keywords: Bouvetøya; NARE 2007/08; Sør-Sandwichøyene; marin biologi; pingviner; sjøfugler

Chinstrap penguin population genetic structure: one or more populations along the Southern Ocean? - Mura-Jornet, Isidora; Pimentel, Carolina; Dantas, Gisele P M; Petry, Maria Virginia; González-Acuña, Daniel; Barbosa, Andrés; Lowther, Andrew D; Kovacs, Kit M; Poulin, Elie; Vianna, Juliana A (BMC Evolutionary Biology, 2018)
Keywords: Bouvetøya; Sørishavet; fugler; genetikk; marin biologi; ornitologi; pingviner

Prey differences drive local genetic adaptation in Antarctic fur seals - Cleary, Alison C; Bester, Marthán; Forcada, Jaume; Goebel, Michael; Goldsworthy, Simon D; Guinet, Christophe; Hoffman, Joseph I; Kovacs, Kit M; Lydersen, Christian; Lowther, Andrew D (Marine Ecology Progress Series, 2019)
Antarctic fur seal (Arctocephalus gazella) colonies are found on sub-Antarctic islands around the continent. These islands experience a range of conditions in terms of physical and biological habitat, creating a natural laboratory to investigate local genetic adaptation. One striking habitat difference is in the availability of Euphausia superba krill as prey, which has led to A. gazella exhibiting a range of diets. A. gazella in some colonies consume exclusively krill, while their conspecifics in other colonies feed mainly on fish and consume few to no krill. To investigate potential adaptations to these different prey fields, reduced representation genome sequencing was conducted on A. gazella from the 8 major colonies. Twenty-seven genomic regions exhibiting signatures of natural selection were identified. Two of these genomic regions were clearly associated with seals living in krill-dominated areas or those in fish-dominated areas. Twenty-two additional genomic regions under selection showed a pattern consistent with prey differences as the driver of selection after historical migrations from krill-dominated habitats where lineages evolved to present krill-poor habitat areas were taken into account. Only 1 of the genomic regions identified appeared to be explained by any other environmental variable analysed (depth). Genomic regions under prey-driven selection included genes associated with regulation of gene expression, skeletal development, and lipid metabolism. Adaptation to local prey has implications for spatial management of this species and for the potential impacts of climate- or harvest-driven reductions in krill abundance on these seals. KEY WORDS: Arctocephalus gazella · Double digest restriction-site associated DNA sequencing · ddRAD · Diet · Euphausia superba · Natural selection
Keywords: Bouvetøya; Sørishavet; genetikk; krill; marin biologi; pelsseler; plankton; zoologi; økosystemer

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis